The Cumulative Amount of Exuded Citrate Controls Its Efficiency to Mobilize Soil Phosphorus - Schack-Kirchner, Helmer; Loew, Caroline A.; Lang, Friederike (Frontiers in Forests and Global Change, 2020)
Root exudation of citrate is discussed as mechanism to mobilize P from the soils’ solid phase. Microbial processes can mitigate the mobilization efficiency of citrate. Due to higher microbial activity in topsoils compared to subsoils, we hypothesized a lower mobilization efficiency of exuded citrate in topsoils than in the subsoils. As a model system we used microdialysis (MD) probes and we followed diffusive fluxes of citrate from the perfusate into the soil and of phosphate from the soil into the dialysate in three soil horizons (Oa, Ah, Bw) of a Fagus sylvatica L. stand Cambisol. Three different MD perfusates with a KCl background concentration have been used: control, 1, and 3 mmol L-1 citric acid. Fluxes have been measured after 24 h, 48 h, and 144 h. The high-citrate perfusate increased the cumulative 144 h P-influx by a factor of 8, 13, and 113 in the Oa, Ah, and Bw horizon, respectively. With the high-citrate treatment, P mobilization efficiency decreased over time, whereas for the low-citrate, P mobilization efficiency had a maximum at day 2. Minimum P mobilization efficiency of citrate was 1:25000 mol phosphate per mol citrate in the Oa horizon between day 2 and 6, maximum was 1:286 in the Bw-horizon during day 2. An increasing citrate efflux over time indicated an increasing sink term for citrate in the soil due to microbial decay or immobilization processes. Cumulative phosphate influx could be fitted to cumulative citrate efflux and soil horizon in a logarithmic model explaining 87 % of the variability. For the first time we could follow the localized P-uptake with citrate exudation over several days. Cumulative citrate efflux as the main control of P-mobilization has been barely discussed yet, however, it could explain some gaps in the role of carboxylates in the rhizosphere. Batch experiments are not capable to elucidate micro-scale dynamic competition for phosphate and carboxylates. In contrast, MD is a promising tool for spatially explicit investigation of phosphate – citrate exchange. In combination with the analysis of microbial properties this technique has a huge potential to identify mobilization processes in soils as induced by citrate.